IMPROVEMENT OF ESTIMATE ACCURACY OF HIGHWAY PROJECTS AND DEVELOPMENT OF A CHAINED FISHER CONSTRUTCION COST INDEX - Nassereddine, Hala Massoud (My University, 2016)
The estimation process represents the critical underpinning of any project. It is a collaborative process carried during different stages. State Highway Agencies (SHAs) strive to develop an engineering estimate that is in line with the market considerations and hopefully, the low bid for the project. One important indicator of the effectiveness and accuracy of the estimating process is how closely it predicts the low bid. The problem of inaccurate SHASs’ estimates is a major concern for legislators. Too low of an estimate leads to uncertainty whether the costs submitted by the contractor is fair and reasonable and should be awarded. Too high of an estimate can mean additional projects must be developed and included in the program to meet published yearly construction amounts. Accurate project estimates are critical, particularly when evaluating the reasonableness of single bids. To measure the credibility of the SHA’s project’s estimate, the Federal Highway Administration (FHWA) established a degree of accuracy standard requiring the engineer’s project estimate to be within 10% of the low bid for at least 50% of the project. The Wisconsin Department of Transportation (WisDOT) has established its own level of accuracy performance standard targeting at least 60% of the projects to be within 10% of the low bid. However, WisDOT bid tabs showed a significant deviation from this desired goal. This continued performance problem resulted in WisDOT reexamining its current estimating process. WisDOT requested that the Construction and Materials Support Center (CMSC) at the University of Wisconsin-Madison assist the Department in the improvement of the accuracy its current estimates. First, WisDOT requested CMSC to look at the project level and improve the engineering estimate accuracy (EEA). In an attempt to achieve the desired objective, the research team analyzed the WisDOT bid tabs at the contract level and created regression models to improve the accuracy of the engineer’s estimate. The underlying concept is dependent on improving the engineer’s estimate by predicting the lowest bid for the project. However, the various statistical analyses performed and the various models formulated to improve WisDOT EEA did not boost the EEA to the 60% threshold. One reason for these results is that the engineer’s estimates themselves contain a high degree of noise or hidden variables such as the number and experience of the personnel who develop the estimates. Thus, inaccuracy of the cost estimates stem not only from the engineer’s estimate. This paper presents the results of this analyses. Following these results, WisDOT requested the research team to expand the research and look at the construction cost index (CCI) as a potential tool for improving the estimating process. CCIs are important SHA to provide an indicator of construction cost escalation over time and to update old bid cost information to current year pricing. FHWA publishes a National Highway Construction Cost Index (NHCCI) based upon cost data from several states for SHA to use. WisDOT uses a CCI to measure the changes in purchasing power of their construction dollar from one year to the next. Currently, WisDOT uses a fixed-weight index to compute the CCI for a fixed basket of seven construction items. However, the current WisDOT CCI is subject to considerable short-term variation and does not accurately reflect the project bid costs that the department is experiencing. This paper presents results of the study requested by WisDOT to develop an approach for calculating a more representative, reliable and objective CCI. The paper presents various approaches to calculating a CCI, highlighting their properties and characteristics. It also outlines the process used to select a representative basket of items to calculate the index and outlines the data preparation steps needed to improve data quality. The recommended methodology uses a chained, two-stage aggregation computation process. The paper compares the newly constructed WisDOT CCI to the old CCI as well as to the NHCCI. The impact from selecting different size baskets of items is also investigated and it is concluded that a basket containing a representative number of items is sufficient to calculate a reliable CCI. Finally, the research team developed time series models to accurately forecast the CCI.